2006
DOI: 10.1128/ec.5.4.723-731.2006
|View full text |Cite
|
Sign up to set email alerts
|

Phosphoinositide 5-Phosphatase Fig4p Is Required for both Acute Rise and Subsequent Fall in Stress-Induced Phosphatidylinositol 3,5-Bisphosphate Levels

Abstract: Phosphoinositide lipids regulate complex events via the recruitment of proteins to a specialized region of the membrane at a specific time. Precise control of both the synthesis and turnover of phosphoinositide lipids is integral to membrane trafficking, signal transduction, and cytoskeletal rearrangements. Little is known about the acute regulation of the levels of these signaling lipids. When Saccharomyces cerevisiae cells are treated with hyperosmotic medium the levels of phosphatidylinositol 3,5-bisphospha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

18
193
0
1

Year Published

2007
2007
2021
2021

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 138 publications
(212 citation statements)
references
References 37 publications
18
193
0
1
Order By: Relevance
“…This is also suggested by studies in yeast, which demonstrated an in vitro or in vivo specificity of the Fig4 phosphatase for position 5 in PtdIns(3,5)P 2 substrate and a marked up-regulation of PtdIns(3,5)P 2 upon expression of Fig4 mutants with substitutions within the Sac phosphatase domain (11,18,41,58). To examine whether Sac3, like Fig4, hydrolyzes PtdIns(3,5)P 2 , we conducted experiments both in vitro and in a cell context.…”
Section: Resultsmentioning
confidence: 79%
See 2 more Smart Citations
“…This is also suggested by studies in yeast, which demonstrated an in vitro or in vivo specificity of the Fig4 phosphatase for position 5 in PtdIns(3,5)P 2 substrate and a marked up-regulation of PtdIns(3,5)P 2 upon expression of Fig4 mutants with substitutions within the Sac phosphatase domain (11,18,41,58). To examine whether Sac3, like Fig4, hydrolyzes PtdIns(3,5)P 2 , we conducted experiments both in vitro and in a cell context.…”
Section: Resultsmentioning
confidence: 79%
“…The consensus CX 5 R(T/S) active site, invariant in mammalian Sac domain containing phosphatases, is positioned within the sixth motif with a sequence 486 CVDCLDRTN. Accordingly, the Sac3 D488A mutant, similarly to a corresponding mutation in Fig4 (11,41), is devoid of phosphatase activity as measured in vitro by the malachite green assay (see below). Unlike the Sac1 proteins, yeast Fig4 and mammalian Sac3 do not display a putative transmembrane sequence, and besides the regions of the Sac phosphatase domain and low complexity, there are no other obvious conserved domains along the Fig4/ Sac3 molecule ( Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…PI(3,5)P 2 is synthesized from PI(3)P by the PI(3)P 5-kinase Fab1/PIKfyve/PIP5K3 (5,6). Fab1 is stimulated by a regulatory complex that contains Vac14 (7,8) and Fig4 (4,9). Surprisingly, the Vac14/Fig4 complex plays two opposing roles in the regulation of steady-state levels of PI(3,5)P 2 .…”
mentioning
confidence: 99%
“…The major cellular function of Sac domain-containing proteins is to modulate intracellular membrane trafficking, including exocytosis, endocytosis and membrane transportation between various intracellular compartments, via hydrolyzing their corresponding phosphoinositide substrates [1,2,7,8]. Synaptojanin 1 and 2 are involved in regulating endocytic vesicle fission and phosphoinositide dephosphorylation [1].…”
mentioning
confidence: 99%